Water Source Partitioning among Trees Growing on Shallow Karst Soils in a Seasonally Dry Tropical Climate - Querejeta, José Ignacio; Estrada-Medina, Héctor; Allen, Michael F.; Jiménez-Osornio, Juan José (Oecologia, 2007)
The sources of water used by woody vegetation growing on karst soils in seasonally dry tropical regions are little known. In northern Yucatan (Mexico), trees withstand 4-6 months of annual drought in spite of the small water storage capacity of the shallow karst soil. We hypothesized that adult evergreen trees in Yucatan tap the aquifer for a reliable supply of water during the prolonged dry season. The naturally occurring concentration gradients in oxygen and hydrogen stable isotopes in soil, bedrock, groundwater and plant stem water were used to determine the sources of water used by native evergreen and drought-deciduous tree species. While the trees studied grew over a permanent water table (9-20m depth), pit excavation showed that roots were largely restricted to the upper 2m of the soil/bedrock profile. At the peak of the dry season, the δ¹ɸO signatures of potential water sources for the vegetation ranged from 4.1 ± 1.1‰ in topsoil to -4.3 ± 0.1‰ in groundwater. The δ¹ɸO values of tree stem water ranged from -2.8 ± 0.3‰ in Talisia olivaeformis to 0.8 ± 1‰ in Ficus cotinifolia, demonstrating vertical partitioning of soil/bedrock water among tree species. Stem water δ¹ɸO values were significantly different from that of groundwater for all the tree species investigated. Stem water samples plotted to the right of the meteoric water line, indicating utilization of water sources subject to evaporative isotopic enrichment. Foliar δ¹³C in adult trees varied widely among species, ranging from -25.3 ± 0.3‰ in Enterolobium cyclocarpum to -28.7 ± 0.4‰ in T. olivaeformis. Contrary to initial expectations, data indicate that native trees growing on shallow karst soils in northern Yucatan use little or no groundwater and depend mostly on water stored within the upper 2-3 m of the soil/bedrock profile. Water storage in subsurface soil-filled cavities and in the porous limestone bedrock is apparently sufficient to sustain adult evergreen trees throughout the pronounced dry season.